Poza granicami schematów. Kilka uwag o polskiej refleksji nad przekładem - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2016)
Going beyond schemas. Some remarks on the Polish reflection upon translation The diversity of Polish voices about translation draws attention to the fundamental problems of translation: 1) the role of the translator in the process of linguistic and cultural transference; 2) the modeling impact of the receiving culture on the target text; 3) respect for the output work and culture in relation to word and text; 4) linguistic and cultural untranslatability; 5) the desire to create a discipline that “would tame” the complex nature of translation in theory and practice. Reflections upon these issues led to interdisciplinary and descriptivity in translation studies. Currently we are dealing with the situation of the repealing of faithfulness in translation as an impossible and unnecessary task. The voices of Polish translators, among others, growing over the centuries, were confirmed by this theoretical reflection. Researchers have announced it in Polish translatory reflection. They represented different methodological, phenomenological and structuralist-semiotic options (for example, Stefania Skwarczyńska and Edward Balcerzan in the years 1965—1981). In their reflections on translation, an essential role has been played by the adoption of two basic assumptions. The first one concerns the autonomy of a literary work, whereas the other one is about interpretation, that is, its full implementation in the process of reading. Within their borders, they pointed to the inevitability of the gradable identity of translation with respect to the original. Key words: Polish translatory reflection, identity, transformations of the original, needs of the receiving literature, repealing of fidelity